Unveiling the anti-inflammatory mechanism of exogenous hydrogen sulfide in Kawasaki disease based on network pharmacology and experimental validation - Ling Yu; Qianwen Luo; Xiaohui Rao; Xiao Xiao; Pinghan Wang (Scientific Reports)
Abstract Kawasaki disease (KD) is a severe pediatric vasculitis leading to coronary artery complications. Hydrogen sulfide (H2S), a recognized endogenous gasotransmitter with anti-inflammatory properties, offers potential as a novel treatment for KD through its cardiovascular benefits. However, the specific effects and underlying mechanisms remain unclear. The objective of present study is to investigate the anti-inflammatory and therapeutic effects of exogenous H2S in KD using network pharmacology and experimental validation. By online database searches, a total of 405 pharmacological targets for H2S, 826 KD-related targets, and 107 potential therapeutic targets of H2S for KD were identified. Through PPI analysis and Cytoscape screening, 9 hub genes were filtered, namely TNF, IL6, JUN, AKT1, IL1B, TP53, NFKB1, MAPK1, and RELA. KEGG pathway enrichment indicated that the TLR4/MyD88/NF-κB signaling pathway may play a crucial role in the therapeutic effects of H2S on KD. Additionally, in vivo experiments confirmed that the treatment of sodium hydrosulfide (NaHS), an H2S donor, markedly improved body weight, reduced inflammatory pathology in the coronary arteries, and downregulated levels of inflammatory cytokines TNF-α, IL-1β, and IL-6. Furthermore, WB analysis confirmed that NaHS inhibited the expression of TLR4, MyD88, NF-κB, and p-NF-κB. In brief, it is the first to reveal that exogenous H2S attenuates the inflammatory response in KD via the TLR4/MyD88/NF-κB pathway, highlighting its potential as a novel therapeutic approach for KD. These findings lay a foundation for further development of H2S-based therapies for KD management.